Determinação da vazão de escoamento superficial na situação atual de urbanização na microbacia do Córrego do Barbado, Cuiabá-MT - São Pedro, Aline Nayara Rodrigues (2017)
Urbanization is a process that entails several complications for the cities, such as floods problem this applicant in urban areas, cause numerous damages for both population and public power.In this way, the study of changes in the hydrological dynamics in the urban space subsidizes the elaboration of solutions to this question. Then this work has as objective to determine the flow of surface runoff as well as to reproduce the design hydrograms for the dry and humid soil in the current urbanization situation in the Córrego do Barbado. The methodology used in this work was an environmental assessment using the VERAH method, which addressed vegetation, erosion, solid waste, water and housing. And the reproduction of the runoff flow and the design hydrographs of the basin with application of the Soil Convervation Service (SCS) method. The results show that the Córrego do Barbado suffers from many problems such as: scarcity of green area in the basin; high rate of urbanization, inefficiency or non-existence of rainwater harvesting systems, etc., having a direct influence on the hydrological behavior of the basin, contributing to the occurrence of flood flooding in the stretch of the Fernando Correa da Costa Avenue stream. The reproduced values of the basin design hydrographs for the return times of 5, 10, 20, 50 and 100 years resulted in 44.47 m3/s, 52.73 m3/s, 62.36 m3/s, 77,01, m3/s, 81.78 m3/s for dry soil and 88.99 m3/s, 100.80 m3/s, 107.32 m3/s, 133.71 m3/s, 148.77 m3/s for wet soil respectively. It can be concluded that this work has data to support management and planning actions to solve the problems of recurrent pluvial drainage in the basin, the study also pointed out that urban occupation impacts not only the environmental quality of the basin but also in the hydrological dynamics of the Córrego do Barbado.